The Possible Non-Mutational Causes of FVIII Deficiency: Non-Coding RNAs and Acquired Hemophilia A - Zimta, Alina-Andreea; Hotea, Ionut; Brinza, Melen; Blag, Cristina; Iluta, Sabina; Constantinescu, Catalin; Bashimov, Atamyrat; Marchis-Hund, Elisabeth-Antonia; Coudsy, Alexandra; Muller-Mohnssen, Laetitia; Dirzu, Noemi; Gulei, Diana; et al. (Frontiers in Medicine, 2021)
Hemophilia type A (HA) is the most common type of blood coagulation disorder. While the vast majority of cases are inherited and caused by mutations in the F8 gene, recent data raises new questions regarding the non-heritability of this disease, as well as how other molecular mechanisms might lead to the development of HA or increase the severity of the disease. Some data suggest that miRNAs may affect the severity of HA, but for some patients, miRNA-based interference might cause HA, in the absence of an F8 mutation. A mechanism in HA installation that is also worth investigating and which could be identified in the future is the epigenetic silencing of the F8 gene that might be only temporarily. Acquired HA is increasingly reported and as more cases are identified, the description of the disease might become challenging, as cases without FVIII autoantibodies might be identified.